Design of a Virtual Based English Learning Application System Reality and Augmented Reality - Hasibuan, Ahmad Riady; Syafrayani, Putri Rizki; Khairani, Suci (Universitas Islam Sumatera Utara, 2024)
Textbook-based learning media makes the learning atmosphere less attractive for students, especially for elementary school students. This causes the transfer of knowledge to be hampered. Advances in information technology have penetrated the world of education which applies information technology as a tool in teaching and learning activities such as visual animations including augmented reality technology. The augmented reality of technology in English learning applications is a solution to attract the interest of elementary school children. This application has two main features, namely learning and quizzes. First, students are given an introduction to objects around the house in English, then asked to work on questions in an augmented reality and virtual reality technology environment. This application carries out several processes which include reading marker symbols using a camera, then carrying out a pre-processing stage, namely the segmentation process for comparing marker symbols. If the marker symbol is an image that is similar to the reference data, the recognition image will be used to display the 3 dimensions of the object. The trial results show that the features of this application work well, and students perceive it as helpful to have this application for learning English.